Ulisses entre as artes visuais e a literatura. Um estudo de obras de José Roberto Aguilar e Lenir de Miranda - CAVALCANTE, Mário Mendes (2011)
The aim of this research is to investigate the possible relationships between visual arts and literature from the study of works produced by the Brazilian artists José Roberto Aguilar (1941-) and Lenir de Miranda (1945-). Both have appropriated the character Ulysses from Homer's Odyssey and produced works using painting. Based on a literature review focused on the history of art, contemporary art theory and intersemiotic translation studies, we focus our study around the concepts of appropriation and expanded field. We conclude that the literary signs are appropriated for the artists in the field expanded of contemporary art as a poetic possibility.